Intense Pulsed Light and Red Light Photo Rejuvenation for Skin Rejuvenation: A Split Face Clinical Trial - Moravvej, Hamideh; Saeedi, Mohammad (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: Intense pulsed light (IPL) has long been used for skin rejuvenation. Photo rejuvenation with red light (with or without photo sensitizer) is a newer noninvasive way for this purpose; but, until now few comparative studies between these modalities have been performed. The aim of this study was to compare efficacy, adverse effects, and compliance of intense pulsed light rejuvenation and red light photo rejuvenation in a homogeneous group of women. METHODS: In this clinical trial, ten female volunteers with Fitzpatrick skin types I, II, and III were enrolled. Patients underwent 6 sessions of IPL rejuvenation at 4-week intervals on one side, and 30 photo rejuvenation sessions (twice a week) with red light on the other side of their face. Improvement of the skin texture and reduction in the wrinkles were determined in two ways. Firstly, by comparing the photographs, and secondly, by measuring the skin elasticity with Reviscometer MPA 9 system, before and after the procedure. RESULTS: Both treatments were associated with improvement in the skin texture and wrinkle depth, but red light was more effective on the nasolabial fold and IPL was more effective on the fine wrinkles. CONCLUSIONS: Red light photo rejuvenation without the use of photosensitizer can be a new, effective and safe procedure for rejuvenation